The Integration of Non-Traditional Security into Ausindo Eagle to Expand Defense Diplomacy between Indonesia and Australia - Aritonang, Alice Agatha Delfreeta; Perwita, Anak Agung Banyu; Aritonang, Sovian; Hendarwoto, Yermia (International Journal of Education, Culture, and Society, 2025)
This study addresses the limited scholarly attention to bilateral military exercises as instruments of defense diplomacy, despite their growing significance for regional security in Southeast Asia. Specifically, it analyzes the role of the AUSINDO EAGLE joint exercises in advancing Indonesia–Australia defense cooperation and in mainstreaming non-traditional security agendas within bilateral defense diplomacy. Adopting a qualitative research design, the study employed purposive sampling of two key historical cases—the inaugural AUSINDO EAGLE exercise in 1993 and the most recent in 2023. Data were collected through document analysis of official military reports, policy statements, and secondary literature, and analyzed using thematic content analysis. The findings demonstrate that AUSINDO EAGLE has progressed from a conventional interoperability-focused joint air exercise into a comprehensive defense engagement encompassing humanitarian assistance and disaster relief. This transformation underscores defense diplomacy’s dual function as both a confidence-building mechanism and an adaptive strategy to address non-traditional security challenges. The study concludes that AUSINDO EAGLE not only consolidates bilateral defense cooperation but also enhances regional stability by broadening the scope of security collaboration. The implications include theoretical contributions to defense diplomacy literature and practical recommendations for policymakers to strengthen joint training programs, expand multilateral participation, and institutionalize HADR frameworks. The study also highlights avenues for future research, particularly comparative analyses with ASEAN-led exercises and empirical fieldwork involving military practitioners.